Analysis of Poverty Correlates and Multi‐Dimensionality in South East Nigeria: New Empirical Evidence From Survey Data. Issue 3 (11th September 2020) - Orji, Anthony; Ogbuabor, Jonathan E.; Nwosu, Emmanuel; Anthony‐Orji, Onyinye I.; Amoji, Nene
Abstract : Using data from the Generalized Households' Survey (GHS), this article analyzed the incidence of multi‐dimensional poverty and its determinants in South East Nigeria. Adopting the Alkire‐Foster methodology and the logit model, the study found that the significant predictors of poverty and deprivation across dimensions include income (less than minimum wage), education, and consumption. The result showed that based on per capita consumption expenditure, over 60 percent of the South East population are living below the used 1.25/day. The pattern of group‐specific poverty headcounts showed that those without formal education are poorer than those with formal education. Seventy percent of those residents in the rural areas were found to be poor as compared with 30 percent poverty level found in the urban areas. Male‐headed households were found to be far poorer than female‐headed households based on poverty headcounts; however, in terms of multi‐dimensional poverty headcounts, female‐headed households are more deprived than the male‐headed households. The result also showed that the multi‐dimensional poverty is exacerbated by being a female‐headed household, living in rural areas with large household size. All of these were found to increase the possibility of being multi‐dimensionally poor. The result also showed that a household with electricity reduces the incidence of multi‐dimensional poverty. The study, therefore, recommended that the government should pay closer attention to female‐headed households and the rural areas by providing the basic amenities to ameliorate their socio‐economic plights. Since the availability of electricity and other infrastructure reduces poverty incidence, it is expedient for the government to make power (electricity) provision and other infrastructure, a major priority.